Usability of Antimicrobial Peptides in Poultry Nutrition - Senay Sarıca (Turkish Journal of Agriculture: Food Science and Technology)
Peptides with antimicrobial properties as an alternative to antibiotics antibiotic growth promoters in poultry nutrition have been studied in recent years. These peptides, which can be supplemented to diet or water, are effective not only against bacteria but also against fungi, viruses and parasites. In this article, the definition, the structures, the types, the sources of production, the application areas, the microorganisms they act on and the mechanism of action of antimicrobial peptides and information about the studies related to their use in poultry nutrition will be given.